2021
DOI: 10.1021/acs.est.1c04431
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Interrogation of Metabolic and Bioenergetic Responses of Early-Staged Zebrafish (Danio rerio) to a Commercial Copper Hydroxide Nanopesticide

Abstract: The use of copper hydroxide nanopesticide can pose exposure risks to aquatic organisms. In this study, the toxicity of a copper hydroxide nanopesticide, compared to conventional copper sulfate at environmentally relevant doses, was evaluated using metabolomics and bioenergetic assays in embryonic zebrafish. At a copper concentration of 100 μg/L, the nanopesticide caused higher mortality and deformity compared to copper ions alone; despite higher copper accumulation, increased metallothionein and elevated ATP-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…The quantitative and visualized results of the JC-1 red/green fluorescence assay showed that DR-MoS 2 and Na 2 MoO 4 significantly induced depolarization of the mt△Ψ m at both low and high concentrations, whereas no impact was evident with DF-MoS 2 (Figures C, S6, S7). The transfer of electrons during mitochondrial respiration is accompanied by the establishment and dissipation of the membrane potential, which is essential for proper OXPHOS function. , The loss of mt△Ψ m after DR-MoS 2 and Na 2 MoO 4 exposure implies that the mitochondrial transmembrane potential was prematurely dissipated, which could directly affect the subsequent phosphorylation process …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantitative and visualized results of the JC-1 red/green fluorescence assay showed that DR-MoS 2 and Na 2 MoO 4 significantly induced depolarization of the mt△Ψ m at both low and high concentrations, whereas no impact was evident with DF-MoS 2 (Figures C, S6, S7). The transfer of electrons during mitochondrial respiration is accompanied by the establishment and dissipation of the membrane potential, which is essential for proper OXPHOS function. , The loss of mt△Ψ m after DR-MoS 2 and Na 2 MoO 4 exposure implies that the mitochondrial transmembrane potential was prematurely dissipated, which could directly affect the subsequent phosphorylation process …”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of Mito-RETC complex I-mediated NADH electron flow by DR-MoS 2 could impede the mitochondrial membrane potential (mt△Ψ m ) formation and subsequent oxidative metabolic reactions. 52 Neither MoS 2 nanosheets nor molybdate at either concentration affected the activity of Mito-RECT complex II, the second component of OXPHOS (Figure 2E). However, Mito-RETC complex III activity was significantly inhibited after exposure to 100 mg Mo/L of DF-MoS 2 or DR-MoS 2 (p = 0.0482/p = 0.0022), although the inhibitory effect of DR-MoS 2 was more pronounced (p = 0.0413 for DF-MoS 2 vs DR-MoS 2 , t test) (Figure 2F).…”
Section: Effect Of Df-mos 2 Dr-mos 2 and Molybdate On Cellular Acti...mentioning
confidence: 92%
See 1 more Smart Citation
“…Glutamine and glutamic acid have similar biological functions. They can participate in the biosynthesis of α-ketoglutarate and can supplement citric acid, malic acid, and other tricarboxylic acid cycle intermediates [ 44 ]. Leucine can be a source of glutamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish ( Danio rerio ) has been widely used as a model organism for the evaluation of toxic effects [ 7 , 8 , 9 , 10 , 11 ]. In our previous study, we found that scopoletin had developmental toxicity to zebrafish embryos and the maximum non-lethal concentration (MNLC) was 18.5 μg/mL; and that scopoletin at 18.5 μg/mL could cause varying degrees of liver degeneration, pericardial edema, muscle degeneration, yolk sac retention, and reduced the blood flow of the zebrafish embryos.…”
Section: Introductionmentioning
confidence: 99%